Interest Premium, Sudden Stop, and Adjustment in a Small Open Economy. Issue 4 (3rd July 2016) - Benczur, Peter; Konya, Istvan
Abstract : This article studies the adjustment process of a small open economy to a sudden worsening of external conditions. The sudden stop is modeled by the use of a highly nonlinear specification that captures credit constraints in a convenient way. The advantage of this approach is that the effects of the shock become highly conditional on the external debt position of the economy. A two-sector model with money-in-the-utility is adopted, thereby making it possible to study sectoral asymmetries in the adjustment process, and also the role of currency mismatch. The model is calibrated to the behavior of the Hungarian economy in the 2000s, and its crisis experience in 2008–11 in particular. Four counterfactuals are calculated: two with different exchange rate policies (a more flexible float and a perfect peg), and both of these policy regimes with smaller initial indebtedness. Overall, the model is able to fit the movements of key aggregate and sectoral macroeconomic variables after the crisis by producing a large and protracted deleveraging process. It also offers a meaningful quantification of the policy tradeoff between facilitating the real adjustment by letting the currency depreciate and protecting consumption expenditures by limiting the adverse effect of exchange rate movements on household balance sheets.